The Rice Effect: Sugarcane Production in Florida Following Rice - José Alvarez; George H. Snyder (EDIS)
Since sugarcane is the principal crop in the rice-sugarcane rotation, researchers at the University of Florida's Everglades Research and Education Center (EREC) conducted experiments to determine the effect of rice production upon the sugarcane plant crop that followed the rice crop. This document summarizes two experiments. The first analysis was based on each producer's records (Alvarez and Snyder, 1984). The second was an experiment in commercial fields (Snyder, et al., 1986). This is EDIS document FE474, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published May 2004.